Redução plena do deôntico ao ôntico - Lindner, Diogo (2008)
The current dissertation has as its main objective an exposition and critical analysis of Charles Kielkopf's translation of the Standard Deontic Logic (SDL) into a normal alethic logic, and the resulting construction of a system of deontic logic that captures Kantian fundamental concepts and principles such as the concept of causal necessity and the formulations of the Categorical Imperative concerning Kingdom of Nature and Kingdom of Ends. Since this process results in an interpretation of aspects of the Kantian philosophy, it has been chosen, initially, a presentation in general lines of these concepts and, considering the difficulties regarding the applicability of a translation process between deontic and ontic principles, it was done necessary also an exhibition concerning the problem of the inferential barriers, as well as of his more immediate consequence, i. e., Jörgensen's Dilemma. In a second moment, it was also made a characterization of normal modal systems, deontic ones and alethic ones, as well as of the notions of translation between logics and of Dawson modelling. The final chapter consists of a critical examination of Kielkopf's proposal, which uses Dawson modelling to develop a deontic logic based on the alethic system K1. Such Dawson modelling allows the definition of a deontic modalities in terms of iterated alethic modalities, therefore this model constitutes a way of avoiding the problems regarding inferential barriers. The development of an alternative for attribution of logical status to deontic concepts doesn't constitute, however, in an innovative aspect of this proposal, such aspect can be founded in the use made by Kielkopf of his formal model as a tool for the investigation of philosophical concepts, such as the Kantian concepts already mentioned.